2007
DOI: 10.2106/jbjs.e.00704
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographic and Magnetic Resonance Imaging to Predict Lumbar Stenosis, Low-Back Pain, and No Back Symptoms

Abstract: This prospective, controlled, masked study of electrodiagnosis and magnetic resonance imaging for older subjects showed that imaging does not differentiate symptomatic from asymptomatic persons, whereas electrodiagnosis does. We believe that radiographic findings alone are insufficient to justify treatment for spinal stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
88
2
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(97 citation statements)
references
References 46 publications
4
88
2
3
Order By: Relevance
“…The pathology of this disease is most typically due to degenerative changes. Haig et al 11 and Geisser et al 12 demonstrated that there was little relationship between central canal size and clinical symptoms among individuals with a clinical diagnosis of lumbar spinal stenosis. Amonoo-Kuofi et al 13 and Agur 14 have reported a small and triangular vertebral foramina with "pinched" lateral angles at L5.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathology of this disease is most typically due to degenerative changes. Haig et al 11 and Geisser et al 12 demonstrated that there was little relationship between central canal size and clinical symptoms among individuals with a clinical diagnosis of lumbar spinal stenosis. Amonoo-Kuofi et al 13 and Agur 14 have reported a small and triangular vertebral foramina with "pinched" lateral angles at L5.…”
Section: Introductionmentioning
confidence: 99%
“…The mean width of the vertebral foramen (as determined in dry bone and radiological study) was ranged between 21.6 to 25.1 mm. Haig et al, 11 Weinstein, 23 Verbiest, 24 and Jane et al 25 noted that lumbar canal width, ranging from 10 to 12 mm might be associated with claudication if additional soft or hard tissue elements encroached on the canal, and they referred to this type of stenosis as "relative" canal stenosis. The diameters observed in the present study were in contrary to those of Williams et al 26 who reported a gradual decrease in measurement between L1 and L5 level, with a greater relative width in females, however, the present study did not show any significant differences in the average widths (means) of lumbar vertebral foramina between males and females.…”
mentioning
confidence: 99%
“…In various studies conducted by Bolender [12], Lee [13] and Haig [14] wherein the spinal canal diameter was measured. They established cut off values in order to diagnose stenosis, <13mm, <10mm and <11.95mm respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This is because the presence of LSS on magnetic resonance imagig (MRI) or computed tomography (CT) scans has been shown to poorly correlate with lower extremity symptoms. [12][13][14][15][16][17][18] Similarly, not all patients with PVD, demonstrated by their arterial brachial index (ABI) measurement on a Doppler ultrasound, have claudication symptoms. 19,20 Moreover, both LSS and PVD can coexist in the same patient, and imaging studies are unhelpful in deciding which must be treated for relief of their claudication symptoms.…”
Section: Verbiestmentioning
confidence: 99%